Dancing Letters and Ticks That Buzz around Aimlessly: On the Origin of Crowding. (September 2014) - Strasburger, Hans
When we see an object, we know where it is. Or do we? Perhaps not in indirect vision, as was observed by the gestalt psychologist Korte in 1923. Objects and object parts appear to 'dance around', and these phenomena may underlie a part of what is called the crowding effect today. From Korte's account of pattern recognition in indirect vision, I select two phenomena: A loss of the positional code for letter parts and a loss of the same for whole letters. Using these examples, I present a novel, speculative explanation for a contradiction in the literature: patterns located more peripherally than a target show more interference than do more centrally located patterns, yet for whole-letter confusions the asymmetry is the other way round. The inward, not the outward, flanker is increasingly confused with a target at increasing target eccentricities. I propose that feature-binding decreases with eccentricity such that free-floating letter parts more often intrude from the periphery and whole letters from the centre. I conclude with a few remarks on computational modelling as, hopefully, a challenge to neural computationalists.